Fabrication and characterization of hand-Made 1´12 splitter based on polymer optical fiber made of polymethyl methacrylate - Mohd Syuhaimi Ab-Rahman; Hadi Guna; Mohd Hazwan Harun; Kasmiran Jumari (Universiti Kebangsaan Malaysia, 2010)
This research was conducted to develop a 1×12 optical splitter based on polymer optical fiber (POF) made from polymethyl methacrylate (PMMA) material as a high efficiency optical signal transmission medium. Basically, the optical device has 1 POF input port and 12 POF output ports in a bundled fiber form. There are several system available in the market which are able to split or couple optical signals transmitted into some different channels, which are all afflicted with certain constrains. However, these systems are too expensive for most applications. The goal of this research was to develop an economical splitter for multi-purpose application over PMMA-POF. Red LED with 650 nm wavelength was injected into the splitter with the aim to analyze the power efficiency of the splitter. A coupling efficiency of 80% was demonstrated. The performance of these hand-made splitters can be improved gradually through experience and practice.